2018- CSA Monitoring: Santa Rita Climate Smart-Village (Honduras) - Bonilla Findji, Osana; Eitzinger, Anton; Andrieu, Nadine; Jarvis, Andrew; Martínez Barón, Deissy; Suchini, José Gabriel (2019)
This dataset contains the files produced in the implementation of the “Integrated Monitoring Framework for Climate-Smart Agriculture” in the Santa Rita Climate Smart Village (Honduras) in April 2018. This monitoring framework developed by CCAFS is meant to be deployed annually across the global network of Climate-Smart Villages to gather field-based evidence by tracking the progress on: